Improved current methods for amplification of DNA from routinely processed liver tissue by PCR. - de Lamballerie, X (1994)
With both a classic DNA preparation protocol (including removal of paraffin wax and protein digestion) and a DNA extraction protocol with Chelex 100, the hepatitis B virus genome was searched for using the polymerase chain reaction (PCR) in 30 samples of paraffin wax embedded liver tissue from patients with chronic hepatitis. The classic protocol was more sensitive than the rapid Chelex 100 procedure (10 v six positive samples). A third protocol, including removal of paraffin wax, protein digestion, and Chelex 100 treatment of the digestion solution before PCR, was more sensitive than the others (16 positive samples). It is concluded that it could therefore be helpful for PCR analysis of paraffin wax embedded liver tissue.